SISTEM KEKERABATAN MASYARAKAT BALI DALAM NOVEL “TARIAN BUMI” KARYA OKA RUSMINI (KAJIAN ANTROPOLOGI SASTRA) - Jafar - Lantowa (Faculty of Humanities, Universitas Jenderal Soedirman, 2017)
This study aims to describe the kinship system of Balinese in novel Tarian Bumi by Oka Rusmini, and uses literary anthropology approach. In analyzing the cultural elements particularly the kinship system of the Balinese in the novel, this study uses descriptive interpretative method by presenting it in description technique. The data were collected from reading and noting technique, and analyzed by using literary anthropology approach with content analysis model. Content analysis was done through inference, analysis, validity and reliability. The results show that the kinship system of Balinese is Patriliniel and Sekasta kinship system. This relationship is clearly illustrated by Telaga descendans of Brahmins who married to Sudra man and became a disgrace and catastrophe for the family. The Sekasta marriage system is opposed by Telaga by marrying a man who was not a descendant of Brahmins. As a result, Telaga is declared out of its Dadia (Brahmin’s family temple). Telaga followed her husband as a Sudra woman as well as his descendants because of the Patrilineal kinship system that governs the lives of Balinese.